Policy implications of resource constraints on the European economy - Kurt Kratena; Mark Sommer (WWWforEurope, 2014)
It is expected that binding biophysical constraints have the potential to slow growth and impede the improvement of other key macroeconomic variables. Using a DYNK (Dynamic New Keynesian) model of the EU27, we study two different environmental policy options and evaluate their impact on environmental as well as socio-economic targets (equity and employment). Macroeconomic simulation models are very useful to discuss alternatives to the status quo in economic theory and policy in the face of increasing resource scarcities and impacts. Scenarios of possible economic futures until 2050 generated on the basis of these models can provide very useful insights. Any feasible scenario that allows for achieving policy targets for resource use without completely failing on economic and social targets requires absolute decoupling of resource use from income or GDP. Therefore, a modelling approach that takes into account the full feedback between the physical flows that are to be reduced and the flows in the economic system needs to be applied. For Europe the reduction of resource use is linked to different policy goals. First of all, the European consumer is embedded into global value chains and thereby directly and indirectly contributes to global resource use. GHG emissions of Europe are still an important part of global emissions and emissions per capita are far beyond a sustainable global level. Security of supply and the risks attached to that are a further issue for a European resource policy. The political targets, formulated in roadmaps for GHG emission reduction and resource efficiency therefore describe significant reductions in resource use linked to domestic production (GHG emissions), as well as to domestic consumption (domestic material consumption, DMC). The main instrument discussed in this context is the introduction of prices/taxes for GHG emissions and for resources like construction minerals and metal ores. At the same time, the problem of 'leakage' is identified in a scenario of an isolated European policy. Higher costs for European producers due to these taxes may lead to relocation of energy and material intensive production. This in turn can hurt labour in Europe and on a global scale lead to the same or even higher resource use and GHG emissions. In the end, the genuine source of leakage is the consumers' demand in Europe. Given this demand, producers outside Europe increase their resource use, if the European producer of energy and material intensive products is not competitive. The socio-economic impact of two alternative policies ('classical green tax' reform, 'environmental fiscal devaluation') is analysed and compared.
Keywords: H; J68; O38; O44; Q48; Q54; Q58; 330; Beyond GDP; Biophysical constraints; CGE models; Ecological innovation; Macroeconomic disequilibrium; Socio-ecological transition; Sustainable growth; Wealth